2012
DOI: 10.4236/abc.2012.24050
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and bioinformatics studies of phosphatidic acid phosphohydrolase from <i>Lagenaria siceraria</i>

Abstract: Phosphatidic acid phosphohydrolase (PAP), EC 3.1.3.4, is the penultimate step in the Kennedy pathway of triacylglycerol (TAG) synthesis leading to the formation of diacylglycerol (DAG), which is a key intermediate in TAG synthesis. We partially purified a soluble PAP from mid maturing seeds of bottle gourd, Lagenaria siceraria. The steps include both anionic and cationic ion exchanger columns. Catalytic characterization of the partially purified PAP revealed that the optimum pH and temperature for activity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…This result further confirmed that the soluble PAP activity is Mg 2+ -independent in bitter melon extract. These assay results confirm the previous observations from crude extract of bitter melon and partially purified bottle gourd PAP that these PAPs are Mg 2+ -independent enzyme [39] , [41] . The overall results suggest that a new class of PAP exists in bitter melon and bottle gourd which is a soluble and Mg 2+ -independent enzyme.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This result further confirmed that the soluble PAP activity is Mg 2+ -independent in bitter melon extract. These assay results confirm the previous observations from crude extract of bitter melon and partially purified bottle gourd PAP that these PAPs are Mg 2+ -independent enzyme [39] , [41] . The overall results suggest that a new class of PAP exists in bitter melon and bottle gourd which is a soluble and Mg 2+ -independent enzyme.…”
Section: Resultssupporting
confidence: 91%
“…These K m and V max values of the purified PAP from bitter melon were approximately 4-fold and 56-fold, respectively, of those obtained from crude bitter melon extract [39]. These K m and V max values of the purified PAP from bitter melon were approximately 3-fold of those obtained from partially purified bottle gourd PAP [41]. The differences in PAP kinetic parameters between the partially purified PAP and crude PAP preparations are in agreement with some observations from previous publications.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This result further confirmed that the soluble PAP activity was Mg 2+ -independent in cottonseed extract. These assay results confirm the previous observations from crude extract of bitter melon and partially purified bottle gourd PAP that these PAPs are Mg 2+ -independent enzyme [12] [17]. The overall results suggest that a new class of PAP exists in cottonseed which is a soluble and Mg 2+ -independent enzyme.…”
Section: Mg 2+ -Independent Activity Of Papsupporting
confidence: 90%
“…In order to achieve this objective, the present study was interested in seeds of some Cucurbitaceous such as C. lanatus, L. siceraria and C. edulis. Although, several studies were carried out on their pharmacological potential (Prajapati et al, 2010) and the various rough levels of nutriments (Nmila et al, 2002;Sabo et al, 2005a, b;Sadou et al, 2007;Ullah et al, 2012), very few works were focused on the biochemical composition of these seeds (Abiodun and Adeleke, 2010). In Benin, previous researches were focused on the agronomic evaluation of some species of Cucurbitaceous used in the foodstuff in Benin (Achigan Dako et al, 2006) in other to develop a model of prediction.…”
Section: Introductionmentioning
confidence: 99%